Storie di rifiuti, rifiuti nelle storie: due prospettive sullo scarto (Altre Modernità, 2020)
Scrap, as a residual and not easy to place element, is a common topic in a great number of works in contemporary fiction, where it takes on a precise meaning: waste. This paper aims to analyse this theme focusing on some emblematic passages of two maximalist novels published at the end of 20th Century: Underworld, by Don DeLillo, and Infinite Jest, by David Foster Wallace.In the former, Nick Shay’s job consists of the disposal of waste, which becomes something that questions the concept of functionality (Scaffai 139). Moreover, waste becomes the tangible equivalent of adolescent traumas, surfacing all over again. In Infinite Jest, the stories told by the drug addicts who live in Ennet House, the real “scraps” of the novel, represent an effort made by characters to re-elaborate narratively their suffering, giving voice to their own experience. Waste symbolizes the return of the rejected, what was relegated to the margins of the community or characters' lives; it becomes a means to advocate for space in the complex plots of the novels.